PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS PADA PT ACE HARDWARE INDONESIA TBK PERIODE TAHUN 2012-2021 - Sri Wulandari; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2023)
This study aims to determine the effect of the work environment and work discipline on employee performance in the administrative division of PT Kehatilab Indonesia Tangerang Selatan, either partially or simultaneously. The results of this study show that: (1) The work environment has a significant effect on employee performance by showing a value of 0.686 (XI). (2) Work discipline has a significant effect on employee performance by showing a value of 0.702 (X2) (3) Work environment and work discipline have a significant effect on employee performance by showing a value of 0.793 (Y). Work environment and work discipline have a significant effect on employee performance with the regression equation Y = 10.375 + 0.667 X1 + 0.597 X2 with the adjusted r square coefficient of determination being 0.495 or 49.5%, while the rest (100% - 49.5% = 505%) are influenced or explained by other variables not included in this study. Based on the results of the F hypothesis test, the value of Fcount > Ftable or (36.345> 3.13) is obtained. In addition, it is known that the significant value is smaller than 0.05 or 0.000 <0.05, so it can be concluded that H0 is rejected Ha is accepted, meaning that there is a significant effect simultaneously between the work environment (X1) and work discipline (X2) on the performance of administration employees at PT. . Kehatilab Indonesia South Tangerang (Y).